(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
This article investigates the problem of mapping in Welfare folklore twentieth century folk, namely in anecdote, estimates of Soviet totalitarian regime. People work conceptualized as a way to protest against the genocide of the Ukrainian people in times of ideological pressure on all national.